2001
DOI: 10.2176/nmc.41.87
|View full text |Cite
|
Sign up to set email alerts
|

Hemifacial Spasm Due to Cerebellopontine Angle Meningiomas. Two Case Reports.

Abstract: A 54-year-old female and a 49-year-old female presented with complaints of hemifacial spasm. Both patients underwent surgery to remove cerebellopontine angle meningiomas. In one case, no vascular compression was observed at the root exit zone. The tumor was removed subtotally leaving residual tumor adhered to the lower cranial nerves. The hemifacial spasm disappeared immediately after the operation. The residual tumor was treated using gamma knife radiosurgery. In the other case, the root exit zone of the faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In patient groups treated with surgery for tumors, Chang et al 3 stated that 2 (3%) of 65 intracranial meningiomas presented with HFS, and Samii and Matthies 20 noted that 4 (0.4%) of 1000 patients with VSs presented with HFS. In groups of patients who underwent radiosurgery, Iwai et al 8 found that facial spasm occurred in 6% of the patients. There is another subgroup of patients with newly developed HFS after radiosurgery for VSs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patient groups treated with surgery for tumors, Chang et al 3 stated that 2 (3%) of 65 intracranial meningiomas presented with HFS, and Samii and Matthies 20 noted that 4 (0.4%) of 1000 patients with VSs presented with HFS. In groups of patients who underwent radiosurgery, Iwai et al 8 found that facial spasm occurred in 6% of the patients. There is another subgroup of patients with newly developed HFS after radiosurgery for VSs.…”
Section: Discussionmentioning
confidence: 99%
“…Nagata et al 16 noted excellent postoperative recovery after resection of benign tumors in the posterior fossa in their 4 patients (100%). Iwai et al 8 reported 2 cases, in which one patient had undergone microsurgery alone and the other patient had microsurgery followed by radiosurgery for residual tumor. Both patients obtained freedom from HFS.…”
Section: Outcomes Of Microsurgery and Radiosurgerymentioning
confidence: 99%
“…Hemifacial spasm commonly results from unilateral vascular compression 7,8) whereas it is rarely caused by ipsilateral pathology adjacent to the REZ of the facial nerve other than vascular compression 2,4,6,10,11,15) . This unilateral hyperac- tive dysfunction of facial nerve is manifested by spasm of the orbicularis oculi that slowly spreads to involve the orbicularis oris and all of the muscles of facial expression, including the platysma.…”
Section: Discussionmentioning
confidence: 99%
“…When the artery is located between the tumor and facial nerve, the artery may be trapped and begin to compress the nerve as the tumor grows. The standard surgical treatment for this tumor and the associated HFS is microsurgical removal of the tumor first, with MVD added selectively according to the anatomy around the CPA 6,11,19) . Tumors remote to the CPA causing HFS are rarely reported and the pathogenic mechanism is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation